2011
DOI: 10.1002/mren.201100013
|View full text |Cite
|
Sign up to set email alerts
|

Polyethylene Nanocomposites Obtained by in situ Polymerization via a Metallocene Catalyst Supported on Silica Nanospheres

Abstract: Polyethylene (PE) nanocomposites were produced through in situ polymerization using bis(n‐butylcyclopentadienyl) zirconium dichloride (nBuCp)2ZrCl2 supported on silica nanospheres (SN) with diameters of 80–100 nm synthesized by the sol–gel method. The metallocene catalyst was either supported directly on the SN or on SN pretreated with methylaluminoxane (MAO). The effect of zirconium loading on the catalytic behavior and polymer properties was studied. High catalytic activities, comparable with homogeneous pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 42 publications
1
23
0
Order By: Relevance
“…When ethylene was polymerized in gas phase over flat Phillips model catalyst (CrO x /SiO 2 /Si(100)), it was reported that a 20 μm thick polyethylene film was produced. The homogeneous dispersion of the active sites and constant polymerization rate during the reaction were attributed as a mechanism for the formation of a relatively smooth homogeneous polymer film . It was also reported that the lack of catalyst support interaction resulted in clustering of the active phase, leading to a formation of highly porous polymer with extensive formation of stress fibrils.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When ethylene was polymerized in gas phase over flat Phillips model catalyst (CrO x /SiO 2 /Si(100)), it was reported that a 20 μm thick polyethylene film was produced. The homogeneous dispersion of the active sites and constant polymerization rate during the reaction were attributed as a mechanism for the formation of a relatively smooth homogeneous polymer film . It was also reported that the lack of catalyst support interaction resulted in clustering of the active phase, leading to a formation of highly porous polymer with extensive formation of stress fibrils.…”
Section: Resultsmentioning
confidence: 99%
“…The preparation techniques for non‐porous solid silica nanoparticles are well documented in the literature. Also, the use of nanometer size silica particles for catalytic olefin polymerization has been reported in recent literature . There was a report that nanosilica supported metallocene catalysts showed higher polymerization activities and slightly larger molecular weight than the micron‐sized porous silica supported catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Melt compounding, where a mixture of polymer and filler is contacted above the glass transition temperature and mechanically mixed, often leads to an unsatisfactory dispersion on account of difficulties in sufficiently agitating the typically highly viscous polymer melts. Such disadvantages can be solved by in situ polymerization techniques, where the polymer is generated in a medium with the dispersed filler . An advanced type of the latter is the polymerization filling technique .…”
Section: Introductionmentioning
confidence: 99%
“…5 µm. Nevertheless, the use of µCT for the characterization of polyolefin particle morphology is still relatively scarce when compared to the electron15, 16 or optical microscopy techniques 17…”
Section: Introductionmentioning
confidence: 99%